Marketing communication in the area of breast and cervical cancer prevention - Cvijović, Jelena; Kostić - Stanković, Milica; Krstić, Goran; Stojanović, Ljupče (Vojnosanitetski pregled, 2017)
Background/Aim. Innovative marketing campaigns and promotional activities can successfully contribute to the improvement of public health by raising the level of general knowledge about health issues and benefits that the change of habits, eradication of undesirable behaviour and regular medical controls have. The focus should be on continuous marketing communication through various mass media or direct communication between medical staff and patients. The aim of this paper was to define the role that various communication channels have in the process of informing and educating the target group in case of breast and cervical cancer prevention. Methods. The survey based on polling a sample of 2,100 female patients of the Serbian Railways Medical Centre was conducted in the period October–December 2013. The questionnaire included questions about demographic characteristics, prevention habits of women, their level of information on that topic and communication channels they prefer. Results. There is a difference among respondents’ awareness level about preventive measures depending on demographic and geographical criteria. The results indicate the existence of variations in frequency of performing gynaecological examinations and Pap tests depending on different age, educational and residential groups. Although the largest percentage of women stated familiarity with the way of performing breast self-examination (78%), the majority of them had never performed mammography or ultrasonography (67%). The greatest number of women were informed about the possibility of preventing breast and cervical cancer by posters or brochures in health institutions (71%) and mass media – television on the first place (74%), then specialized magazines about health (48%), radio (48%), web sites about health (42%), and daily newspapers (34%). The respondents consider the Ministry of Health and health institutions as the most responsible subjects for education of women about cancer prevention, while the self-initiative was given the least importance. Conclusion. Determined informing habits of the target group, their prevention habits and attitudes on the subject should be used as the basis for planning and implementation of prevention marketing campaigns that would be the most effective.
Keywords: breast neoplasms; uterine cervical neoplasms; health promotion; communications media